2021
DOI: 10.3389/fimmu.2020.629722
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Burden and Immunotherapy: Impact on Immune Infiltration and Therapeutic Outcomes

Abstract: Cancer immunotherapy has revolutionized the treatment landscape in medical oncology, but its efficacy has been variable across patients. Biomarkers to predict such differential response to immunotherapy include cytotoxic T lymphocyte infiltration, tumor mutational burden, and microsatellite instability. A growing number of studies also suggest that baseline tumor burden, or tumor size, predicts response to immunotherapy. In this review, we discuss the changes in immune profile and therapeutic responses that oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 197 publications
(250 reference statements)
3
77
0
Order By: Relevance
“…However, additional studies are still warranted to refine the phenotype of cells expressing each inhibitory receptor combination and explore how to apply this fact into clinical intervention. Immune infiltration in TME is regarded as a crucial factor of immunotherapy response (3,36). Combined estimation of biomarkers independently predicting response has been betterstudied in recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…However, additional studies are still warranted to refine the phenotype of cells expressing each inhibitory receptor combination and explore how to apply this fact into clinical intervention. Immune infiltration in TME is regarded as a crucial factor of immunotherapy response (3,36). Combined estimation of biomarkers independently predicting response has been betterstudied in recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor burden (or tumor size) predicts response to immunotherapy in patients with cancer. A large TME and a small TME are characterized by different cell populations and responses to specific interventions [ 186 ]. Radiologic imaging such as computed tomographhy (CT) is the most commonly used technology for tumor burden monitoring even though it has limitations for the evaluation of the response to immunotherapy.…”
Section: Cxcl8 As a Prognosis Biomarker In Cancer Therapymentioning
confidence: 99%
“…A possible explanation for the interaction of our new high/low-risk classification with irT effect on survival may be related to tumor burden. Several studies indicated that tumor burden and number of metastatic sites are negative predictive factors for immunotherapy efficacy [ 26 , 27 , 28 ]. It is suggested that the immune penetrance is lower when the tumor burden is high and that advanced tumors’ microenvironments have greater populations of immune suppressive cells [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%